Relationship among noise exposure, sensitivity, and noise annoyance with job satisfaction and job stress in a textile industry. (June 2019) - Abbasi, Milad; Yazdanirad, Saeid; Habibi, Peymaneh; Arabi, Saeid; Fallah Madvari, Rohollah; Mehri, Ahmad; Poursadeghiyan, Mohsen; Ebrahimi, Mohammad Hossein; Ghaljahi, Maryam
The purpose of this study was to investigate the relationship among noise exposure, sensitivity, and noise annoyance with job satisfaction and job stress among the workers of a textile industry. In this study, Weinstein's Noise Sensitivity Scale, Noise Annoyance Questionnaire (recommended based on ISO 15666-2003), Health and Safety Executive (HSE) Job Stress Questionnaire, and Job Satisfaction Scale were used to determine the degree of noise sensitivity, noise annoyance, occupational stress, and job satisfaction, respectively. The results showed that there was a significant difference in the mean of job satisfaction, job stress, noise sensitivity, and noise annoyance between case and control groups. The results of multivariate analysis of covariance showed that noise exposure, noise sensitivity, and noise annoyance can justify 0.09, 0.19, and 0.06 of the variance of job stress, respectively. These variables also could justify 0.09, 0.12, and 0.05 of the variance of job satisfaction, respectively. Noise sensitivity had the greatest effect on increasing the occupational stress and job satisfaction.